2018
DOI: 10.1016/bs.pmbts.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Arrestins: Introducing Signaling Bias Into Multifunctional Proteins

Abstract: Arrestins were discovered as proteins that bind active phosphorylated G protein-coupled receptors (GPCRs) and block their interactions with G proteins, i.e., for their role in homologous desensitization of GPCRs. Mammals express only four arrestin subtypes, two of which are largely restricted to the retina. Two nonvisual arrestins are ubiquitous and interact with hundreds of different GPCRs and dozens of other binding partners. Changes of just a few residues on the receptor-binding surface were shown to dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…In addition, upon activation of β2-AR, PKA mediates β2-AR phosphorylation activating two major signaling pathways: Gβγ/PI3K/Akt and Ras/Raf/ MEK/ERK, which are involved in the occurrence and infiltration of HCC [31][32][33]. Meanwhile, the studies suggested that β2-AR mediated cAMP/PKA/ERK1/2 signaling promotes the growth of liver cancer cells [34]. In combination with the current study, the results showed that the ratios of p-ERK/ERK and p-Akt/Akt were significantly higher in DEN-induced HCC mice and in terbutaline-stimulated LX-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, upon activation of β2-AR, PKA mediates β2-AR phosphorylation activating two major signaling pathways: Gβγ/PI3K/Akt and Ras/Raf/ MEK/ERK, which are involved in the occurrence and infiltration of HCC [31][32][33]. Meanwhile, the studies suggested that β2-AR mediated cAMP/PKA/ERK1/2 signaling promotes the growth of liver cancer cells [34]. In combination with the current study, the results showed that the ratios of p-ERK/ERK and p-Akt/Akt were significantly higher in DEN-induced HCC mice and in terbutaline-stimulated LX-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Arrestins have two major functions in GPCR regulation. First, receptor desensitization and internalization through recruitment of clathrin-coated pits [ 64 , 65 ] and second, the recruitment and activation of effectors such as MAPK and SFKs ([ 63 ] and reviewed in [ 66 , 67 ]). However, the concept of purely arrestin-based signaling has been recently challenged [ 68 ].…”
Section: Src Activation Through a Gpcr–arrestin Complexmentioning
confidence: 99%
“…Two arrestin subtypes were found to be expressed in the retina, arrestin-1 and -4. These arrestins are specialized in binding light-activated phosphorylated rhodopsin and suppressing G protein activation [200,201]. It has been demonstrated that retinal and nonretinal arrestins mediate suppression of GPCRs, suggesting a common mechanism for desensitizing ARs [202].…”
Section: Role Of β-Ars In the Retinamentioning
confidence: 99%